Hemicelluloses and associated compounds determine gall functional traits. (17th August 2020) - Bragança, G. P. P.; Alencar, C. F.; Freitas, M. S. C.; Isaias, R. M. S.
Abstract: The intriguing questions concerning gall development refer to the processes of the remodelling of the host plant organ. Such processes involve the restructuring of cell walls and can be influenced by phenolics, indole‐3‐acetic acid (IAA) and reactive oxygen species (ROS). Alterations in cell walls demand the interference in the coupling of cellulose fibrils and hemicelluloses (xyloglucans) at specific stages of gall development. In addition to cell wall remodelling, hemicelluloses, such as the, xyloglucans and heteromannans can act as reserve carbohydrates, while xylans provide rigidity to the secondary cell walls. Developmental traits of the lenticular, fusiform and globoid galls on Inga ingoides (Fabaceae) were analysed using anatomical, cytometric, histochemical and immunocytochemical tools. Phenolics, IAA and ROS accumulated in similar gall tissue compartments, and may have influenced the restructuring of hemicelluloses and pectins. Contrary to expectations, cell wall flexibility regarding the dynamics of xyloglucans and cellulose fibrils does not relate to a temporal scale. The detection of xyloglucans in nutritive cell walls relate to carbohydrate nutritional resources to the galling insect, while xylans were associated to the lignified cell walls. Heteromanans were not detected, either in non‐galled or galled tissues. The patterns of cell expansion during gall development relied on the relationship among phenolics, ROS and IAA with the hemicelluloses (xyloglucans and xylans) and cellulose fibrils. Although cell wall dynamics is specific to each gall morphotype in I. ingoides, the xyloglucans function as carbohydrate reserve to the gall inducers, which constitutes a functional trait common to the three morphotypes. Abstract : Spatial detection of xyloglucans indicates their role in gall nutritional requirements, while ROS and auxin accumulation sites relate to changes in cell elongation axis.